TRANSFORMATIONAL LEADERSHIP AND RESISTANCE TO ORGANISATIONAL CHANGE AMONG NURSING STAFF: A SYSTEMATIC LITERATURE REVIEW - Mohd Noor, Norizun; Abdullah, Fatin Aina Leong; Soon , Lean Keng (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2026)
Organisational change in healthcare frequently provokes psychological and behavioural resistance among nursing staff, potentially undermining implementation effectiveness and workforce well-being. Transformational leadership has been widely recognised as a leadership approach capable of mitigating such resistance by fostering trust, empowerment, and psychological readiness for change. However, empirical evidence remains fragmented, particularly regarding the mechanisms and contextual factors influencing this relationship within nursing populations. This systematic literature review examines how transformational leadership influences resistance to organisational change among nursing staff, identifies mediating psychological mechanisms, and explores contextual moderators shaping leadership effectiveness. Guided by the SALSA framework and reported in accordance with PRISMA 2020 guidelines, 243 records were identified from Scopus, Web of Science, ScienceDirect, and Google Scholar. Following screening and eligibility assessment, 25 empirical studies published between 1993 and 2025 were included for synthesis. Thematic analysis revealed that transformational leadership consistently reduced resistance to change through enhanced trust, empowerment, communication clarity, and psychological safety. Organisational culture, hospital type, and demographic characteristics moderated these effects. This review contributes to organisational psychology and counselling-informed leadership literature by clarifying how transformational leadership operates as a psychosocial mechanism in managing resistance to change among nursing staff. Practical implications for leadership development and change implementation are discussed.